Squamous cell carcinoma of the scalp: Analysis of reconstructive techniques - Raposio, Giorgio; Baldelli, Ilaria; Gualdi, Alessandro; Antonini, Andrea; Raposio, Edoardo (Acta Biomedica Atenei Parmensis, 2024)
Background: Surgical therapy of squamous cell carcinomas (SCC) is based on complete excision of the neoplasm and its immediate suitable reconstruction. The aim of this work was to evaluate the possibility of creating a reconstructive algorithm in cases of scalp SCC, depending on the amplitude of the tumour, based on a literature’s review.Methods: A literature search was carried out using the databases of Pubmed, Scopus and Cochrane.Results: Based on the experiences reported in the literature, it was possible to structure a decision-making algorithm that summarizes the various steps involved in the choice of the most suitable reconstructive surgical therapy.Conclusion: The algorithm described we hope will be of reference or help to less experienced reconstructive plastic surgeons.